The employment relationship in an (almost) structureless labour market: the case of domestic work - Suleman, F. (2015)
Although domestic workers are generally engaged in informal contracts with hourly and daily wages, some have formally written contracts and are paid monthly. Hourly and daily wages suggest flexible arrangements, whereas the monthly payment system may be used to develop a stable relationship. Using original data from a sample of domestic workers in Portugal, we offer empirical evidence on predictors of four types of arrangement that combine formality and stability. The results from multinomial logistic regression indicate that the wage level is a crucial predictor of the type of contract. Households seem to make a trade-off between stable contracts and high-level wages. However, the odds of being given a formal and stable contract increase when domestic workers have specific skills or are responsible for care, and there are trust-related issues. Our findings suggest that the use of flexible and informal labour has its limitations even in an activity perceived as non-skilled.